Concerns in Supply Chain Management: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
The control of the flow of goods is alluded to as logistics, and it  comprises all operations that turn raw materials into completed  commodities. It entails assertively simplifying an industry's  supply-side activities in increases customer importance and  receive a market position. Inter integration is necessary for timely  deliveries, and marketing will play a vital role. The task ahead is  to try and make this connectivity work. We provide a framework  of logistics, as well as practical difficulties and research areas for  the future. To exemplify the concepts presented, research papers  executed at different businesses but also involving multiple  participants of supply chain operations are utilized. In this  manner, SCM is worried with general business better operations  and marks a new method to top managers and interplay with other  stakeholders.
Keywords: Customer Satisfaction; Order Management; Supply Chain; Supply Chain Management; Supply Demand